AFLP markers for meat traceability of cattle in the Chinese market. (September 2018) - Zhao, Jie; Li, Tingting; Xu, Zhenzhen; Wang, Zhiying; Yang, Shuming; Chen, Ailiang
Abstract: Traceability can play an important role in preventing food fraud, reducing food risk, and increasing consumer's confidence in food safety. In this study, an amplified fragment length polymorphism procedure was used to identify 89 individuals from the most representative cattle breeds present in the Chinese market. Eight pairs of combined primers were obtained, which were E04M06, E04M44, E04M49, E33M48, E33M49, E39M06, E39M44, and E39M49. These eight primers produced a total of 1095 polymorphic fragments, and each one of the primers could successfully distinguish all the test individuals and the six breeds assessed. Highlights: AFLP marker was used to identify individuals and breeds in the Chinese market. Each combined primers could successfully to identify individuals and breeds. Statistical data analysis could help to verify the effect of the AFLP markers.